Gambyong Lengger Dance in the Lengger Graduation Ritual Ceremony in Giyanti Helmet Wonosobo Regency - Kristina Dwi Handayani; Sestri Indah Pebrianti (Universitas Negeri Semarang, 2023)
Gambyong Lengger dance is a dance created specifically for the Lengger Graduation Ritual Ceremony. This ceremony must be attended by Lengger Giyanti dancers. The dance has a distinctive form performed through its performance elements. The purpose of this research is to examine the performance form of the Gambyong Lengger dance. This research used a descriptive qualitative method with an Ethnocoreology approach. Data collection techniques are observation, interviews, and documentation. Data validity techniques were tested through triangulation of time, techniques, and sources. Data analysis techniques include data reduction, data presentation, and data verification. The results show that the Gambyong Lengger dance performance form is classified as a traditional folk dance in Giyanti Hamlet. The movements were adopted by the Gambyongan movements. In addition, the accompaniment used Cakepan Ladrang Pangkur Padhang Bulan, the makeup uses is corrective makeup, and the costumes use Lengger Giyanti costumes. The suggestion to Sanggar Rukun Putri Budhoyo is that there is a need for variations and additions to the variety of Gambyong Lengger dance movements. Therefore, after the dancers legally become lengger dancers, they can demonstrate their skills in dancing lengger with a dance duration that is not short.